2012
DOI: 10.1128/jvi.05347-11
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Local Pandemic H1N1/2009 Influenza Virus Lineages Revealed by Whole-Genome Analysis

Abstract: Virus gene sequencing and phylogenetics can be used to study the epidemiological dynamics of rapidly evolving viruses. With complete genome data, it becomes possible to identify and trace individual transmission chains of viruses such as influenza virus during the course of an epidemic. Here we sequenced 153 pandemic influenza H1N1/09 virus genomes from United Kingdom isolates from the first (127 isolates) and second (26 isolates) waves of the 2009 pandemic and used their sequences, dates of isolation, and geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 24 publications
11
103
0
Order By: Relevance
“…H1N1 influenza virus (strain A/England/195/2009) was grown in Madin-Darby canine kidney (MDCK) cells in serum-free DMEM supplemented with 1 g/ml trypsin. The H1N1 influenza virus strain used (A/England/195/2009) was isolated by Public Health England in the United Kingdom in April 2009 (22). The virus was harvested 3 days after inoculation and stored at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…H1N1 influenza virus (strain A/England/195/2009) was grown in Madin-Darby canine kidney (MDCK) cells in serum-free DMEM supplemented with 1 g/ml trypsin. The H1N1 influenza virus strain used (A/England/195/2009) was isolated by Public Health England in the United Kingdom in April 2009 (22). The virus was harvested 3 days after inoculation and stored at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Although some global phylogenetic analyses have suggested that a stable influenza virus source population could exist in tropical regions such as East and Southeast Asia [3,4], more recent regional studies focused on Hong Kong and southern China have not yielded convincing evidence of viral persistence in these localities, nor of the consistently higher levels of circulating genetic diversity expected of a source population [6,7] (figure 2). Finally, while small chains of influenza A/H1N1 transmission persisted between the summer and autumn waves of the 2009 pandemic in the UK [26], the time interval between waves was unusually short, such that they are unlikely to represent a general phenomenon.…”
Section: (A) Viral Persistencementioning
confidence: 99%
“…The rapidity of evolution, in combination with the increasing availability of genome-scale sequence data and new computational tools for phylogenetic analysis, facilitate the inference of the evolutionary history and spatial spread of IAVs, in turn providing a better understanding of the patterns and processes that underpin epidemics (2)(3)(4)(5)(6)(7)(8). Eighteen antigenically distinct hemagglutinin (HA) subtypes of influenza viruses have been identified to date (9,10).…”
mentioning
confidence: 99%